Volume 3: Biomedical and Biotechnology Engineering 2019
DOI: 10.1115/imece2019-11944
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Mechanical Properties of PCL-Based Nanofiber Mats Using Atomic Force Microscopy

Abstract: Polymeric scaffolds aid in creating an environment for cell proliferation and differentiation in tissue engineering applications by acting as temporary artificial extracellular matrices (ECMs) for cells to form functional tissue. Many studies have reported that cell behavior can be significantly affected by the physical and chemical properties of a given scaffold. Therefore, the mechanical and structural properties of these scaffolds must be characterized. Polymeric solutions, such as polycaprolactone (PCL), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As such, further studies would provide insight into the exact molecular composition of the individual nanofibers in these scaffolds. AFM studies were able to quantify the mechanical properties of individual fibers [ 19 ]. The differences in mechanical properties observed in this study have the same trends as indicated in previous studies reported in the literature [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, further studies would provide insight into the exact molecular composition of the individual nanofibers in these scaffolds. AFM studies were able to quantify the mechanical properties of individual fibers [ 19 ]. The differences in mechanical properties observed in this study have the same trends as indicated in previous studies reported in the literature [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%